2011
DOI: 10.4049/jimmunol.1003981
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Role of SERPINB9 in Cytotoxic Protection of Human Mesenchymal Stem Cells

Abstract: Clinical trials using allogeneic mesenchymal stem cells (MSCs) are ongoing for the purpose of providing therapeutic benefit for a variety of human disorders. Pertinent to their clinical use are the accessibility to sufficient quantities of these cells allowing for repetitive administration, as well as a better understanding of the specific mechanisms by which allogeneic MSCs evade host immune responses that in turn influence their life span following administration. In this report, we sought to characterize an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…After 24 hours incubation, the cells were harvested, washed three times, and then used in the T‐cell proliferation assay. The anti‐CD3/CD28 proliferation assay was performed as previously described . Isolated peripheral blood mononuclear cells (PBMCs) were reconstituted (at 100,000–200,000 cells/well in a 96‐well‐plate) with RPMI complete medium (RPMI 1640, supplemented with 10% FBS, 1% penicillin‐streptomycin, and 1% l ‐glutamine), stimulated to proliferate with anti‐CD3/CD28 antibodies (6 μg/ml) (eBioscience, San Diego, CA) and cocultured with irradiated (3,000 rad) CB‐MSC for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hours incubation, the cells were harvested, washed three times, and then used in the T‐cell proliferation assay. The anti‐CD3/CD28 proliferation assay was performed as previously described . Isolated peripheral blood mononuclear cells (PBMCs) were reconstituted (at 100,000–200,000 cells/well in a 96‐well‐plate) with RPMI complete medium (RPMI 1640, supplemented with 10% FBS, 1% penicillin‐streptomycin, and 1% l ‐glutamine), stimulated to proliferate with anti‐CD3/CD28 antibodies (6 μg/ml) (eBioscience, San Diego, CA) and cocultured with irradiated (3,000 rad) CB‐MSC for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that the expression of Spi6 is required for the protection of transplanted MSC from allospecific CTL and subsequent survival and immunosuppressive activity [134]. Expression of transgenic PI9 protected both mouse [134] and human MSC [135] from CTL killing. Importantly, transgenic PI9 improved the survival and function of MSC after transplantation to allo-specific recipient mice [134].…”
Section: Transplantation and Autoimmunitymentioning
confidence: 95%
“…PI-9 is also expressed in inflammatory cells [121] and in human peripheral blood mesenchymal stem cells [122]. It is also present in cells infected by cytomegalovirus, Epstein-Barr virus and the BK polyomavirus [123][124][125] as well as in endothelial and mesothelial cells [126] and dendritic cells [119].…”
Section: Expression Of Pi-9 In Different Cell Typesmentioning
confidence: 99%
“…The former may be achieved by RNA interference (RNAi) or antisense technology to knock down PI-9 gene expression. The successful use of siRNA to inhibit the expression of PI-9 has been described in stem cells [122] and in breast cancer [84]. However, the development of siRNA-based therapies has fallen out of favor following the Phase III failure of Bevasiranib, which targeted the expression of vascular endothelial growth factor (VEGF) for the treatment of age-related wet macular degeneration.…”
Section: Downregulation Of Pi-9 Expression and Activitymentioning
confidence: 99%